The Analysis of Authority Abuse that Results in State Financial Loss in the State Administrative Law & Islamic Law Framework - Arief Moelia Edie (Unissula, 2024)
Implementation of duties and functions for the Government is a constitutional obligation. So that every task carried out must be based on the norms stated in the constitution. Holding a position as a leader means there is a mandate that must be held accountable. The aim of this research to analyze state financial losses resulting from authority abuse within the legal framework of state administration from a positive legal perspective in Indonesia and an Islamic legal perspective. The type of research used was normative juridical. Authority abuse is basically an act against the law (the concept of a criminal act) accompanied by mens rea (malicious intent). The emergence of losses to state finances in the legal aspect of state administration requires the restoration of state finances and redressing the causes of state financial losses. So in state administrative law, the aspect of improving the system is a very important thing to do. In Islam, position means power which has implications for the lives of society as a whole, office holders are God's representatives in the human world because the only one who has true power is God. In Islamic criminal law, authority abuse is an act that approaches the crime of corruption.